Development of a 5-DOF arc welding robot. (2016) - Li, Tao; Guo, Fayong; Luo, Minzhou; Ceccarelli, Marco; Chen, Saixuan; Fu, Long; Liu, Xiao; Wang, Meiling
In this paper, a new 5-DOF arc welding robot is introduced by looking at aspects of mechanical design, control system and handheld welding teaching (HWT) method. The structure of this robot is inspired by the functionality of selective compliance assembly robot arms. With the aim to achieve user-oriented HWT, magnet clutches and encoders are adopted into the transmission chains with large reduction ratio. In addition, a gravity balance mechanism is implemented in the robot design to reduce the efforts of operators. The processing of HWT operation is presented with an optimal space arc interpolation algorithm. Two main design characteristics of this robot are low-cost and easy-operation features as compared to conventional 6-DOF industrial robots. Finally, experiments are discussed from laboratory testing the welding performance and results are used to validate the efficiency of the proposed solution.